A new entrant in ketene family: Generation of 2‐(3‐Oxo‐allyl)‐isoindole‐1, 3‐dione and their [4+2] Cycloadditions with 1, 3‐Diazabuta‐1, 3‐dienes. Issue 2 (4th January 2023) - Naikoo, Rayees Ahmad; Sharma, Rashmi; Kumar, Rupesh; Bhargava, Gaurav
Abstract: The manuscript describes a synthetic route for the formation of 5‐(methylisoindole‐1, 3‐dione) pyrimidinones by [4+2] cycloaddition reactions of functionalized 1, 3‐diazabuta‐1, 3‐dienes with 2‐(3‐Oxo‐allyl)‐isoindole‐1, 3‐dione generated in situ from phthaloylalanine and tosyl chloride using triethylamine as a base. The functionalized 5‐(methylisoindole‐1, 3‐dione) pyrimidinones were further explored in the deprotection of amines to afford a variety of 5‐methylamino pyrimidinones. The synthesis of such functionalized pyrimidinones is significant as they have a wide range of pharmacological profiles and are valuable as organic synthons. Mechanistic insights are also proposed for the given synthetic methodology. Abstract : The manuscript describes the formation of 5‐(methylisoindole‐1, 3‐dione) pyrimidinones by [4+2] cycloaddition reactions of functionalized 1, 3‐diazabuta‐1, 3‐dienes with 2‐(3‐Oxo‐allyl)‐isoindole‐1, 3‐dione generated in situ from phthaloylalanine and tosyl chloride using triethylamine as a base. The functionalized 5‐(methylisoindole‐1, 3‐dione) pyrimidinones were further explored in amine deprotection to afford a variety of 5‐methylamino pyrimidinones. The synthesis of such functionalized pyrimidinones is significant as they have a wide range of pharmacological profiles and are valuable as organic synthons.